Association Between Blood Pressure Classification Using the 2017 ACC/AHA Blood Pressure Guideline and Retinal Atherosclerosis. (19th May 2021) - Matsuoka, Satoshi; Kaneko, Hidehiro; Yano, Yuichiro; Itoh, Hidetaka; Fukui, Akira; Morita, Kojiro; Kiriyama, Hiroyuki; Kamon, Tatsuya; Fujiu, Katsuhito; Seki, Hikari; Michihata, Nobuaki; Jo, Taisuke; et al.
Abstract: Background: We aimed to explore the association between the blood pressure (BP) classification defined by the 2017 American College of Cardiology (ACC)/American Heart Association (AHA) guideline and the prevalence of retinal atherosclerosis. Methods: This study was a retrospective observational cross-sectional analysis using the JMDC Claims Database. We analyzed 280, 599 subjects not taking any antihypertensive medications. According to the 2017 ACC/AHA guideline, each subject was categorized as having normal BP ( n = 159, 524), elevated BP ( n = 35, 603), stage 1 hypertension ( n = 54, 795), or stage 2 hypertension ( n = 30, 677) using the BP value at the initial health checkup. Retinal photographs were assessed according to the Keith–Wagener–Barker system. Results: The median age was 46 years, and 50.4% subjects were men. Retinal atherosclerosis, defined as Keith–Wagener–Barker system grade ≥1, was observed in 3.2% in normal BP, 5.2% in elevated BP, 7.7% in stage 1 hypertension, and 18.7% in stage 2 hypertension. Compared with normal BP, elevated BP (odds ratio [OR], 1.30; 95% confidence interval [CI], 1.23–1.38), stage 1 hypertension (OR, 1.71; 95% CI, 1.64–1.79), and stage 2 hypertension (OR, 4.10; 95% CI, 3.93–4.28) were associated with a higher prevalence of retinal atherosclerosis. Among 92, 121 subjects without obesity, high waist circumference, diabetes mellitus, dyslipidemia, cigarette smoking, and alcohol consumption, elevated BP (OR, 1.34; 95% CI, 1.19–1.51), stage 1 hypertension (OR, 1.79; 95% CI, 1.61–1.98), and stage 2 hypertension (OR, 4.42; 95% CI, 4.00–4.92) were associated with a higher prevalence of retinal atherosclerosis. This association was observed in all subgroups stratified by age or sex. Conclusions: Our investigation suggests that retinal atherosclerosis could start even in individuals with elevated BP and stage 1 hypertension.